Law beyond the state dynamic coordination, state consent, and binding international law - Pavel, Carmen E. (New York, NY Oxford University Press, 2021)
At the dawn of the twenty-first century, international politics is increasingly governed by legal rules and institutions. Yet widespread skepticism of its value and transformative potential, and sometimes outright hostility towards it abound. This book provides a normative justification for international law. Namely, it argues that the same reasons which support the development of law at the domestic level, namely the promotion of peace, the protection of individual rights, the facilitation of extensive, complex forms of cooperation and the resolution of collective action problems also support the development of law at the international level. The book offers moral and legal reasons for states to improve, strengthen, and further institutionalize the capacity of international law. The argument thus engages in institutional moral reasoning. It also shows why it should matter to individuals that their states are part of a rule-governed international order. When states are bound by common rules of behavior, their citizens reap the benefits. International law encourages states to protect individual rights and provides a forum where they can communicate, negotiate, and compromise on their differences in order to protect themselves from outside interference and pursue their domestic policies more effectively, including those directed at enhancing their citizen's welfare. Thus, international law makes a critical, irreplaceable, and defining contribution to an international order characterized by peace and justice"--
Hume's dynamic coordination and international law -- Normative judgment, realism, and international law -- The international rule of law -- The compatibility of constitutional democracy and international law -- Constitutionalism and pluralism : two models of international law.
Includes bibliographical references and index.
Keywords: Constitutional law. -- Electronic book; International law; Rule of law